Interrelación de la ciencia histórica y el ambiente - Martínez Castillo, Róger (2007)
The area of interest of historical science is increasingly changing historians have begun to analyze historical sources, through issues related to socio-environmental problems. Environmental science studies the relation between society and its natural background in time and space, the application of development models or the big socio- economical phases and its respective lifestyle, ways and relations of productions empowerment and consumption,within a socio-cultural context.